EFEKTIVITAS PENGGUNAANMODEL PEMBELAJARAN TALKING STICK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI KELAS VIII MTs YPKS PADANGSIDIMPUAN - Ermila Lubis (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
ABSTRACT This study aims to describe of effectiveness of using talking stick learning model on students’ mathematical problem solving ability at the eighth grade students of YPKS Padangsidimpuan. The research was conducted by applying experimental method with 25 students as the sample and they were taken by using cluster random sampling technique from 127 students. Observation and test were used in collecting the data. Based on the data analysis, it was found that: (1) the average of using talking stick learning model was 3.77 (very good category) and (2) the average of students’ mathematical problem solving ability before using talking stick learning model was 44.67 (poor category) and after using talking stick learning model was 85.25 (very good category). In the other word, there is increasing of students’ mathematical problem solving ability by using talking stick learning model. It means, using talking stick learning model was effective to increase students’ mathematical problem solving ability. Key words: talking stick learning model, mathematical problem solving ability